El derecho de acceso a la justicia comunal en las comunidades nativas del distrito de Punchana 2018-2022 - Reátegui del Aguila, Estrella Isabel Alessandra (2025)
The research aimed to determine whether the right of access to communal justice constitutes an autonomous right in the indigenous communities of the Punchana district, Loreto, during the period 2018 2022. A qualitative approach with a non-experimental design and descriptive scope was used, utilizing documentary analysis and structured interviews with communal authorities and community members. The results show that 90% of participants recognize this right as autonomous, in accordance with Article 149 of the Constitution and international treaties. They highlight the existence of statutes that define offenses and sanctions, and hierarchical structures that guarantee order in the administration of justice. However, cases of homicides, femicides, domestic violence, and land invasions require coordination with the ordinary justice system, revealing the need to strengthen inter institutional coordination. It is concluded that communal justice is a pillar of autonomy and cultural identity, and it is recommended to provide training, logistical support, and resources to consolidate its effective and intercultural exercise.